Development and Evaluation of a Fusion Polyprotein Based on HspX and Other Antigen Sequences for the Serodiagnosis of Tuberculosis - Zhou, Fangbin; Xu, Xindong; Cui, Xiaobing; Pan, Weiqing (Frontiers in Immunology, 2021)
Background: The lack of suitable diagnostic tools contributes to the high prevalence of tuberculosis (TB) worldwide. Serological tests, based on multiple target antigens, represent an attractive option for diagnosis of this disease due to their rapidity, convenience, and low cost. Methods: Measures to reduce non-specific reactions and thereby improve the specificity of serological tests were investigated, including blocking antibodies against common bacteria in serum samples and synthesizing polypeptides covering non-conserved dominant B-cell epitopes of antigens. In addition, a fusion polyprotein containing HspX and eight other antigen sequences was constructed and expressed to increase overall sensitivity of the tests. Results: Inclusion of Escherichia coli lysate partially increased the specificity of the serological tests, while synthesis and inclusion of peptides containing non-conserved sequences of TB antigens as well as dominant B-cell epitopes reduced non-specific reactions without a decrease in sensitivity of the tests. A polyprotein fusing HspX and eight other antigen sequences was constructed and displayed 60.2% sensitivity, which was higher than that of HspX and the other individual antigen segments. Moreover, the specificity of the polyprotein was 93.8%, which was not significantly decreased when compared with HspX and the other individual antigen segments. Conclusions: The roles of the fusion polyprotein in the humoral immune response against TB infection were demonstrated and provide a potential novel approach for the development of TB diagnostics.